Pengaruh Strategi Promosi dan Kualitas Pelayanan terhadap Minat Konsumen dalam Pemilihan Produk Asuransi - Dimas Muhammad Ramdani; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of the financial services industry requires insurance companies to improve their promotional strategies and service quality to attract consumer interest. This study aims to analyze the influence of promotional strategies and service quality on consumer interest in choosing AXA Mandiri insurance products at Bank Mandiri Rancaekek Branch. The study used a quantitative method with a survey approach. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The results showed that promotional strategies and service quality had a positive and significant effect on consumer interest, both partially and simultaneously. Service quality had a more dominant influence than promotional strategies. It was concluded that increasing consumer interest in AXA Mandiri insurance products requires effective promotions as well as professional and reliable service